Detection of Fibrinogen Degradation Products by Use of Antibody Coated Latex Particles - Melliger, E. J (Thrombosis and Haemostasis, 1970)
A method for rapid determination of fibrinogen split products in human blood basing on agglutination of antibody coated latex particles is described. It’s sensitivity corresponds to that of Ouchterlony plates (17 μg/ml plasma). The result is available within 1 hr after drawing of blood. The method is semiquantitative with a at least as good reproducibility as the haemagglutination inhibition method. The reaction kinetics follow the principle of optimal proportion in a precipitin system.46 healthy people and 36 patients with various diseases were tested with the described method. 3 controls and 12 patients gave positive agglutination reactions that could not be attributed to the presence of split products. The mechanism of these side reactions which could be distinguished from the reactions due to fibrinogen degradation products is discussed. In the plasma of 10 patients split products could be demonstrated by the latex agglutination technic which was also successfully used to control the course of chronic intravascular coagulation in a patient with disseminated cancer of stomach. On account of the obtained results the method can be recommended as a fairly sensitive screening test for rapid bedside detection of fibrinogen degradation products.